Soil-ecological conditions of the north taiga flat-mound bog, Western Siberia - Raudina, Tatiana V. (Acta biologica sibirica)
Of particular interest in the north of Western Siberia are frozen flat-mound bogs. Being formed in a transitional climatic zone, on the southern front of the permafrost zone, these frozen peatlands may turn out to be highly reactive upon thawing and deliver high amounts of solutes to the hydrologi-cal network. A detailed study of a flat-mound bog was carried out in a key area of about 3 hectares (Purovsky district, Yamalo-Nenets Autonomous Okrug). The soil-ecological conditions of the site are described, as well as the effect of spatial heterogeneity on the composition and properties of soils. Us-ing topographic mapping and photogrammetry, it was identified that the bog surface is characterized by distinct microtopography (mounds-hollows-thermokarst subsidence with a percentage areas ratio of 49:30:21, respectively). Small-scale variations in ecohydrological settings, microtopography, and vegetation affect the distribution of nutrients, organic carbon in soils, and DOC (dissolved organic carbon) in bog waters. The main soil types are Dystric Hemic Cryic Histosols and Dystric Hemic His-tosols (Gelic) found on mounds and in subsidence, respectively. If the peat thickness decreases to 40–60 cm, then Spodic Histic Turbic Cryosols (Albic, Arenic) and Histic Turbic Cryosols (Albic, Arenic) form. In hollows and fens, Dystric Epifibric Histosols, Spodic Histic Turbic Cryosols (Arenic), and Gleyic Histic Entic Podzols (Turbic) are the most common. The proportion of soils with frozen peat is no more than 20% of the area of the key site and permafrost lies deeper, in the underlying rocks. It was found that carbon stocks within the key area vary from 31.1 to 91.3 kg/m2. The maximum values are observed in transit subsidences/hollows between mounds, where water is discharged. Concentrations of macro-microelements in bog waters vary depending on microform types. For some elements (e.g., DOC, Fe, Al, B, Si, Ti, V, Rb, Sb, Cs, REEs (rare earth elements), Pb, Th, U), they are approximately equal or 1.5–2 higher on the mounds. The export of DOC and other elements in permafrost areas is primarily controlled by the residence time of water and movement ways along the profile. In addition to this, the physicochemical properties of peat and biomass, which are also higher on mounds, influ-ence the distribution and accumulation of nutrients.